Bird community responses to vegetation heterogeneity following non-direct regeneration of Mediterranean forests after fire (ARDEA, 2011)
Mediterranean forests are highly resilient to fires, showing a rapid recovery after disturbance. However, in some cases direct tree regeneration fails leading to radical changes in landscape composition. In this study, we evaluated the impact of landscape changes on the conservation value of bird species using the new landscape mosaic arising from non-direct regeneration after a fire. We used data from a large fire that occurred in central Catalonia (NE Spain) in 1998. The fire affected about 26,000 ha of a land mosaic mainly covered by Black Pine Pinus nigra forests and farmland dominated by cereal crops. We used line transects to estimate bird abundance and gathered information on dominant vegetation covers and landscape variables. Redundancy analysis (RDA) and generalized linear models were used to explore how the measured environmental variables explain bird species abundance and to analyze how post-fire heterogeneity in vegetation affected the conservation value of the bird community. Factors describing the main patterns in the post-fire landscape explained up to 31.2% of the total variability in bird community composition and described three main groups of bird species sharing similar ecological requirements. Additionally, 71% of the studied species significantly responded to one of the first three vegetation gradients distinguished in the study area. Finally, the conservation value of the bird community significantly decreased in areas dominated by Q. humilis resprouters and significantly increased in shrubland areas. Overall, our results suggest that large fires affecting non-direct regenerating forest types lead to a new and radically different mosaic landscape offering new opportunities to species with unfavourable European conservation status.